MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI METODE SUKU KATA BAGI ANAK KESULITAN BELAJAR KELAS I DI SDN 03 BANDAR BUAT PADANG - Sutrina, Asep Ahmad Sopandi, Rahmatrisilvia (Universitas Negeri Padang, 2013)
This research is backraund by problems a child's learning difficulties first grade at SDN 03 Bandar Buat Padang are having trouble reading the words.This study uses the approach Single Subject Research, by design AB and techniques of data analysis using visual analysis chart. These results indicate that the method syllable able to improve the ability to read words in teaching reading to children learning difficulties class I SDN 03 Bandar Buat Padang.